Culture fermentation of Lactobacillus in traditional pickled gherkins: Microbial development, chemical, biogenic amine and metabolite analysis - Alan, Yusuf (Springer, 2019)
Fermented cucumber pickles are the lactic acid fermentation products formed through the influence of microorganisms present in the environment. This study investigated the impacts of starter cultures, namely, Lactobacillus plantarum, Lactobacillus pentosus and Lactobacillus paraplantarum, typically utilized for the fermentation of traditional pickled gherkins, on fermentation process. The chemical (pH, total acidity and salt) and microbiological (total mesophilic aerobic bacteria, lactic acid bacteria and yeast-mould) changes were observed against the control sample during fermentation process. Moreover, the amounts of biogenic amines (BAs) and metabolites formed as a consequence of fermentation were determined using HPLC. It was found that the chemical analyses provided similar results for all the samples. The amount of total mesophilic aerobic bacteria and yeast-mould colonies in pickle sample containing L. plantarum 49 strain appeared to reduce significantly. The amount of BAs was the lowest for the pickle samples where L. plantarum strains were added. The amount of BAs was below the toxic value that could affect human health. More BAs were synthesized as the fermentation period increased. Lactate was seen to exist in the samples when pyruvate was present, and acetoin was converted into 2.3-butanediol during the fermentation period. It was concluded that the pickle sample for which L. plantarum 49 strain was used displayed a better fermentation profile (i.e., metabolite and biogenic amines) than the remaining samples. Producing a more delicious and reliable product using such characteristics of L. plantarum strains in pickled gherkins is believed to significantly contribute to the food industry. © 2019, Association of Food Scientists & Technologists (India).
Keywords: Biogenic amines; Lactobacillus; Metabolite; Pickled gherkins